Ways to Enhance Students’ Learning Activities in the Context of Higher Education - Naviy, Liza; Rakisheva, Gulmira M.; Stukalenko, Nina M.; Murzina, Saule A.; Duisenbina, Assem T.; Koshanova, Marash T.; Kazhatova, Guldana N. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
The article aims to study scientific and methodological features of the ways to enhance students’ learning activities in the context of higher education. The study’s theoretical significance is derived from the in-depth analysis of the development of students’ learning activity. The study offers the framework of characteristics for the concept of “students’ learning (cognitive) activity". The main used methods were: analysis, peer-assessment, self-assessment. The interview method was used to make a cognitive profile of the participants, taking into account their psychological characteristics. The authors developed and scientifically tested educational model based on module curricula and interactive teaching methods to enhance students’ learning activity. The authors also reflected the dynamic of the learning activity of the students with disabilities participating in the experiment. The results proved the effectiveness of the developed model of enhancing students’ learning activity by using interactive teaching methods. It was concluded that the module curricular and active teaching methods help enhance students with disabilities’ learning activity and make them more responsible in respect to the results of their study.